Mounted police community patrols - Bradford, Ben (UK Data Service, 2015)
This data collection contains two different datasets. The first dates relates to a telephone survey of local residents in six areas that formed the test and control sites in a quasi-experiment that tested the effect of mounted police community patrols on public 'trust and confidence' in the police. The second dataset pertains to a programme of Systematic Social Observation of mounted and foot police patrols in the same areas and also other police districts. Files relating to the two datasets are included in different zip folders. Mounted police are a feature of public policing around the world. Police on horseback are used primarily in public-order police work, particularly in the policing of large crowds, as well as for a number of other functions such as urban patrols. Mounted police represent a symbol of physical force as well as a connection to past eras of policing. They are thought to calm crowds and avert disorder in ways ‘standard’ police activity cannot. They are also among the most poorly-understood tools in modern public police work. In current conditions of austerity mounted police are, like many other police units or activities, under threat of retrenchment or elimination. Yet policy decisions are being undertaken without recourse to evidence, since virtually no focused research has ever been conducted with mounted police. There is no empirical basis on which to make claims regarding their utility. This project will investigate the ways in which mounted police work is experienced in the UK through a unique observational methodology, alongside focus groups with police officers and citizens. This research will build an evidence base for future strategies and priorities regarding mounted policing. The project is supported by the Association of Chief Police Officers (ACPO) and mounted police units across the UK.